Remarks on quadratic equations in Banach space - Ioannis K. Argyros (International Journal of Mathematics and Mathematical Sciences)
We find new sufficient conditions for the uniqueness of solutions of quadratic and in general multilinear equations in a Banach space X, by assuming the existence of a certain limit of linear operators in a suitable subspace of X.